Order Imbalances and Market Efficiency: Evidence from the Taiwan Stock Exchange - Lee, Yi-Tsung; Liu, Yu-Jane; Roll, Richard; Subrahmanyam, Avanidhar (Journal of Financial and Quantitative Analysis, 2004)
Data from the Taiwan Stock Exchange identify the originator of each submitted order, and there are no designated dealers or specialists. We study marketable order imbalances, i.e., the net order flow resulting from trades that demand immediacy. We distinguish imbalances by trader type (individuals, domestic institutions, foreign institutions) and by the usual size of each trader's order. Day-to-day persistence in order imbalance is strongest for small foreign institutions and weakest for large individual traders. Such persistence emanates both from splitting orders over time and from herding, and there is little evidence that aggregate price pressures from such persistence last beyond a trading day, indicating that de facto market making is quite effective. We attempt to discern which types of traders are de facto liquidity providers, which are likely to be informed, and which trade for liquidity reasons. The evidence indicates that all trader classes are successful market makers, large domestic institutions conduct the most informed trades, and large individuals are noise or liquidity traders.